Krwawa karuzela (Władimir Zazubrin, „Drzazga”) - Zywert, Aleksandra (Studia Rossica Posnaniensia, 2015)
This article presents a comparative analysis of Vladimir Zazubrin’s story titled The Splinter (1923) and its contemporary screen adaptation, i.e. Alexandr Rogozhkin’s film The Chekist (1992), in the context of the Russian nation’s tragedy during the formation of a new socio-political system. Just as Zazubrin text is a peculiar testimony to a certain epoch, Rogozhkin’s film (if one also takes into account the date of its premiere) is a picture that warns contemporary people so as to prevent them from repeating their predecessors’ mistakes.